2016
DOI: 10.1016/j.rppede.2016.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Congenital intrahepatic portosystemic shunt diagnosed during intrauterine life

Abstract: Objective:To report a patient with prenatal diagnosis of portosystemic shunt; a rare condition in humans.Case description:17-Day-old female infant admitted for investigation of suspected diagnosis of portosystemic shunt, presumed in obstetric ultrasound. The hypothesis was confirmed after abdominal angiography and liver Doppler. Other tests such as echocardiography and electroencephalogram were performed to investigate possible co-morbidities or associated complications, and were normal. We chose conservative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(27 citation statements)
references
References 11 publications
0
26
0
1
Order By: Relevance
“…In humans, although both intrahepatic and extrahepatic congenital shunts have been observed, a congenital portosystemic shunt, which accounts for HE, is very rare [10,11]. In contrast, an acquired large portosystemic shunt is observed occasionally in patients who exhibit portal hypertension.…”
Section: Development Of Spontaneous Portosystemic Shuntmentioning
confidence: 99%
“…In humans, although both intrahepatic and extrahepatic congenital shunts have been observed, a congenital portosystemic shunt, which accounts for HE, is very rare [10,11]. In contrast, an acquired large portosystemic shunt is observed occasionally in patients who exhibit portal hypertension.…”
Section: Development Of Spontaneous Portosystemic Shuntmentioning
confidence: 99%
“…Congenital porto‐systemic venous shunts (CPSSs) are a vascular malformation, in which blood from the gastrointestinal circulation partially or completely bypasses the hepatic circulation and drains directly into a systemic vessel, most commonly the inferior vena cava 1,2 …”
Section: Introductionmentioning
confidence: 99%
“…In 1995, Laverdière et al 6 reported the first case of anomalous fetal abdominal venous drainage. Currently, it is estimated that only 10% of cases are diagnosed during intrauterine life; however, most of these diagnoses are made during the investigation of other complications or associated anomalies 2,5 . Still, classifying the types of CPSSs into intra‐ and extra‐hepatic CPSS remains difficult, with no universal consensus 2,7 …”
Section: Introductionmentioning
confidence: 99%
“…El proceso tan complicado del desarrollo de la vena cava y su estrecha relación con el desarrollo del saco vitelino pueden explicar el origen de esta rara anomalía congénita y explicaría la alta incidencia de drenajes venosos en la VCI suprarrenal (3) . La incidencia de esta afección se estima en uno de cada 30,000 nacimientos y se asocia con otras malformaciones como la gastrointestinal, genitourinaria, ósea y cardiovascular (4) . En el 2018 se registró en la literatura mundial 39 casos de Abernethy tipo I y 22 casos de Abernethy tipo II (5) .…”
Section: Introductionunclassified